SULTAN ISKANDAR DJABIR SYAH: FROM MALINO CONFERENCE TO THE MINISTER OF INTERNAL AFFAIRS OF NEGARA INDONESIA TIMUR (Paramita: Historical Studies Journal, 2016)
This study aims to reconstruct the political participation of Iskandar Djabir Syah (the 47thSultan of Ternate) in the establishment of the State of Eastern Indonesia. The results showed that: (1) the participation of Sultan of Ternate Iskandar Djabir Syah in the unitary state started in the early independence of the Republic of Indonesia; it was characterized by conducting Malino and Denpasar conferences in 1946. The establishment of the Eastern Indonesia State became the political inspiration for Iskandar Djabir Syah to involve as the senate member of the Eastern Indonesia State/NIT representing North Maluku, as well as one of its designers. (2) As one of the leaders who agreed to the idea of van Mook to form a federalist country in the Malino and Denpasar conference, so that when the Eastern Indonesia State was formed, he was appointed as the Minister of Internal Affairs in the cabinet of J.E. Tatengkeng for 1949 to 1950 periods. (3) Malino to Denpasar Conference in 1946 that was initiated by H.J. van Mook was the Dutch effort to establish the states in order to realize the United States of Indonesia (Republik Indonesia Serikat/RIS) based on Linggarjati Agreement. At the conference, it was formed the Eastern Indonesia State (Negara Indonesia Timur/NIT) covering the areas of Sulawesi, Small Sunda (Bali and Nusa Tenggara) and the Maluku Islands. Fokus kajian ini menguraikan beberapa peristiwa politik yang melibatkan Iskandar Djabir Syah seperti konferensi Malino dan Denpasar hingga terpilih menjadi menteri dalam negeri Indonesia Timur pada periode 1949-1950.  Hasil penelitian menunjukkan (1). Partisipasi Sultan Ternate Iskandar Djabir Syah dalam negara kesatuan dimulai sejak awal kemerdekaan Republik Indonesia, ditandai dengan diselengarakannya konperensi Malino dan Denpasar 1946. Terbentuknya Negara Indonesia Timur kemudian menjadi inspirasi   politik bagi  Iskandar Jabir Syah untuk melibatkan diri sebagai anggota senat NIT mewakili Maluku Utara, sekaligus merupakan salah satu disainernya. (2). Sebagai salah satu tokoh yang menyetujui gagasan van Mook untuk membentuk negera federalis dalam  konperensi Malino dan Denpasar, sehingga ketika terbentuknya Negara Indonesia Timur diangkat menjadi Menteri Dalam Negeri pada kabinet J.E. Tatengkeng periode 1949-1950.  (3). Konferensi Malino hingga Denpasar pada tahun 1946  yang diprakarsai oleh H.J. van Mook merupakan upaya Belanda mendirikan negara–negara bagian dalam rangka mewujudkan Negara Indonesia Serikat (RIS) berdasarkan Persetujuan Lingarjati. Dalam konferensi tersebut dibentuklah Negara Indonesia Timur (NIT) meliputi wilayah Sulawesi, Sunda Kecil (Bali dan Nusa Tenggara) dan Kepulauan Maluku.